2018
DOI: 10.1002/jnr.24321
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits affect the influences of intensity perception and emotional responses on hedonic rating and preference rank toward basic taste solutions

Abstract: This study aimed at determining, based on independent predictors of taste intensity and emotional response, whether individual personality traits could affect prediction models of overall liking and preference rank toward basic taste solutions. Sixty-seven participants rated taste intensities (TI) of four basic-taste solutions at both low and high concentrations, and of plain water. Emotional responses toward each sample were measured using a self-reported emotion questionnaire (SE), facial expressions (FE), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Regarding emotions, Prescott (2017) pointed out that personality traits, such as granularity or alexithymia, had an impact on the perceived or elicited emotions. Also, Scott, Burgess, and Tepper (2019), Samant andSeo (2018), andHerz (2011) found that taste perception, hedonic and emotional responses were affected by the personality traits. Scott et al (2019) found that the acceptance of pungent spices was highly related to 1) PROP taster status, 2) personality traits such as sensation seeking and food adventurousness, and 3) emotions as wellbeing and disgust.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding emotions, Prescott (2017) pointed out that personality traits, such as granularity or alexithymia, had an impact on the perceived or elicited emotions. Also, Scott, Burgess, and Tepper (2019), Samant andSeo (2018), andHerz (2011) found that taste perception, hedonic and emotional responses were affected by the personality traits. Scott et al (2019) found that the acceptance of pungent spices was highly related to 1) PROP taster status, 2) personality traits such as sensation seeking and food adventurousness, and 3) emotions as wellbeing and disgust.…”
Section: Introductionmentioning
confidence: 99%
“…Cells with gustation receptors (CGRs) and related gustation transmission elements have been proposed in oral cavity and tongue surface. [2] Some instruments are designed to imitate gustation functions of the animals, such as electronic tongue using a multiple sensor array, for certain chemical component qualitative and quantitative analysis from measured solutions. [3] These artificial electrical instruments still present certain accuracy and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Preference rank is based on an effective choice of the samples that is ordered by the volunteer from the lesser to the more likeable sample and provides understanding of the choice. In this study, Samant and Seo () examined whether models describing the abovementioned evaluation of basic taste solutions (salt, sour, sweet and bitter) are influenced by personality types, such as extroverts versus introverts, neurotics versus the emotionally stable. Indeed, they observed that personality types, in particular neuroticism and extraversion, can modulate the evaluation of taste intensity and evoked emotions on the prediction models of overall liking and preference rank toward basic taste solutions.…”
mentioning
confidence: 99%